Analysis of Etichal Moral Education Values and Linguistic in The Poem “Zuhdiyyat” by Abu Al-‘Atahiyyah - Nurfalah, Fauzan; Wiwaha, Rizzaldy Satria; Rusmana, Dadan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The Abbasid Dynasty achieved numerous accomplishments. Many aspects thrived during the Abbasid era, particularly in knowledge and scholarship, including the fields of science, health, religious studies, and literature. During this period, many Europeans traveled to the Abbasid realm to seek knowledge. Therefore, this research aims to discuss one of the literary works that emerged during the Abbasid era, specifically poetry written by the renowned poet Abu Al-‘Atahiyyah, who was a celebrated literary figure of his time. Additionally, the research methodology used is a literature study, with scholarly works and books serving as the references for the study. In his poetry, there are many moral messages, and the Arabic language used remains close to classical Arabic rules. Abu Al-‘Atahiyyah was known for his asceticism and skill in poetry, which led to the creation of numerous poems containing moral educational values about human asceticism. His poetry also features a poetic style that is easy to understand.